Improvement of RBVT-R Routing Protocol in VANET - Yuanlong Chen; Jianfei Ge; Nanjie Liu; Haitao Zhao (Dianxin kexue)
The location-based routing protocol RBVT-R was analyzed. Aiming at the defects of RBVT-R routing protocol during the process of routing establishment and packet forwarding, an improved algorithm of RBVT-R was proposed. This method has improved the flooding mechanism by attaining road traffic density independently during the process of routing establishment. A packet forwarding scheme based on direction and location forecast was proposed during the process of packet forwarding, and had solved the problem of repeated transmission of packets in the same section. The simulation results show that the proposed improvement strategy can effectively enhance the average packet delivery ratio and end-to-end delay.